Diagnosis of Raider Capture to Ensure Business Entities Economic Security in the Conditions of Modern Challenges - Sergienko, Olena; Tatar, Maryna; Bilotserkivskyi, Oleksandr; Stepurina, Svitlana (University of national and world economy, Sofia, Bulgaria, 2020)
The analysis of economic entities interaction for counteraction to raiding is carried out, stages of raiding development in Ukraine and their characteristics are determine, resonant raider attacks in Ukraine during various global challenges and imbalances are analyzed. The aggregation of factors and parameters of threats to economic entities security in relation to raiding counteraction is carried out. The approaches and estimation methods of factors and parameters of raider capture threats are analyzed. The influence of threat parameters on the enterprises raider capture risk is assessed and the influence of parameters which characterize the raiding threats on the q-Tobin index, which characterizes the investment attractiveness, is determined.
Keywords: assessment of factors and parameters; business entities; interaction of business entities; raider attacks; raiding counteraction; threats